Cohort profile: Aichi regional sub-cohort of the Japan Environment and Children's Study (JECS-A). Issue 11 (12th November 2019) - Ebara, Takeshi; Yamada, Yasuyuki; Shoji, Naoto; Ito, Yuki; Nakagawa, Atsuko; Miyachi, Taishi; Ozaki, Yasuhiko; Omori, Toyonori; Suzuki, Sadao; Kojima, Masayo; Ueyama, Jun; Tomizawa, Motohiro; et al.
Abstract : Purpose: Effects of fetal, perinatal and childhood environment on the health of children at birth and during later life have become a topic of concern. The Aichi regional sub-cohort of the Japan Environment and Children's Study (JECS-A) is an ongoing birth cohort of pregnant women and their children which has been used to provide unique data, as adjunct studies of JECS, on multifaceted potential factors affecting children's health. Participants: The JECS-A is part of the JECS which follows a total of 100 000 pairs of children and their mothers (fathers' participation is optional) across 15 regions in Japan. In JECS-A, of the 8134 pregnant women living in Ichinomiya City and Nagoya City, Japan, a total of 5721 pregnant women and their 5554 children were included. Sociodemographic and psychological data as well as biological specimens were collected from the pregnant women and their spouses (if available) in the cohort during their pregnancy. Information on children included in the JECS-A was collected from their mothers and includes demographic, behavioural, childcare, psychological and psychiatric data. Urine extracted from disposable diapers and anthropometric data were also obtained from the children. Findings to date: A similar distribution trend for age at delivery was confirmed between the pregnant women enrolled in the JECS-A and the national statistics of the relevant areas. However, differences in education level and household income were observed. A total of 5502 children remained in the cohort at 18 months after delivery. Compared with the national statistics, the basic demographics of the children in the cohort represented the population in the study areas. Future plans: The enrolled children in the JECS-A will be followed until the age of 13 years. The studies that come from JECS-A will complement JECS and bring novel results with a high level of generalisability.